Herschel/PACS observations of the host galaxy of GRB 031203 - Symeonidis, M.; Oates, S.; de Pasquale, M.; Page, M.; Wiersema, K.; Starling, R.; Schady, P.; Seymour, Nick; O'Halloran, B. (2014)
We present Herschel/PACS observations of the nearby (z = 0.1055) dwarf galaxy that has hosted the long gamma-ray burst (LGRB) 031203. Using the PACS data, we have been able to place constraints on the dust temperature, dust mass, total infrared (IR) luminosity and IR-derived star formation rate (SFR) for this object. We find that the GRB host galaxy (GRBH) 031203 has a total IR luminosity of 3 × 1010 L⊙ placing it in the regime of the IR-luminous galaxy population. Its dust temperature and specific SFR are comparable to that of many high-redshift (z = 0.3–2.5) IR-detected GRB hosts (Tdust > 40 K; sSFR > 10 Gyr−1); however, its dust-to-stellar mass ratio is lower than what is commonly seen in IR-luminous galaxies. Our results suggest that GRBH 031203 is undergoing a strong starburst episode and its dust properties are different to those of local dwarf galaxies within the same metallicity and stellar mass range. Furthermore, our measurements place it in a distinct class to the well-studied nearby host of GRB 980425 (z = 0.0085), confirming the notion that GRB host galaxies can span a large range in properties even at similar cosmological epochs, making LGRBs an ideal tool in selecting samples of star-forming galaxies up to high redshift.